Pripovedništvo na maturi iz slovenščine in problem vrednotenja v šolskem eseju - Koron, Alenka (Jezik in slovstvo, 2019)
The article focuses on prescribed narrative texts for the Matura examination from 1995 to 2019. It sheds light on the frequency of the appearance of narrative texts in the selection (in comparison to dramas) and the literary historical, generic and thematic diversity of such texts. It also examines the need to expand the selection and the possibilities for doing so. Particular attention is devoted to assessment as one of the goals of the systemic didactics of literature, and to the problem of its practical realisation in the school essay as the most complex form of literary examination on the secondary school level.
Keywords: cilji; izbor literarnih besedil; književnost; sistemska didaktika književnost; slovenščina; splošna matura; šolski esej